An Evaluation of the Internship Learning Model to Improve the Competence of Higher Education Graduates - Tjitjik Rahaju; Eva Hany Fanida; Muhammad Farid Ma'ruf; Novi Marlena; Siti Atika Rahmi; I Made Yudhiantara; Abdul Rahman Abdul Latip (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2024)
Increasing the competence of graduates is a significant problem in the evaluation of study programs related to the absorption of graduates in the world of work. This problem can be answered by implementing an innovative internship program and collaborating with various partners. The stipulation of the Minister of Education and Culture of the Republic of Indonesia Number 3 of 2020 concerning National Higher Education Standards, which regulates apprenticeship as a form of learning outside the classroom, aims to provide practical experience to students and reduce the low absorption of graduates in the world of business and industry. This research examines the evaluation of the certified apprenticeship program in the 2019 Public Administration Undergraduate Study Program, which is analyzed using evaluation theory (Dunn), which includes six indicators: effectiveness, efficiency, adequacy, alignment, responsiveness, and accuracy. This research is descriptive research with a qualitative approach. The results showed that things need to be improved, especially in terms of efficiency. This research contributes to the importance of commitment and attention to study programs in collaborating with stakeholders to improve the quality of graduates through internship programs. Suggestions for this research are the need to increase collaboration with external parties related to apprenticeship activities to expand the apprentice network. In addition, it is necessary to increase street vendor guidance activities between supervisors and street vendor students, which are carried out intensively.